Gender-Specific Stressors and Coping Strategies in Adult Education with Migrants in Germany - Vukadin, Florian; Tománek, Pavol (Cross-Cultural Education Studies, 2025)
The increasing migration to Europe faces countries with the challenge of successfully integrating the people who have decided to stay. In Germany, the nation with the most immigrants, integration work is carried out by a variety of workers (full-time employees, lateral entrants and volunteers). These semi-professionals lack the relevant experience and qualifications and are therefore more susceptible to stress and declining motivation. Differences between men and women in this area are assumed and analysed both descriptively and inferentially in an empirical approach with 254 respondents. The results show a difference between men and women in the perception of stress, triggers and levels, but no significant differences in coping strategies were recognised. Recommendations for a better working environment can be derived from the findings in order to successfully carry out systemically relevant integration work at a high level. The findings highlight the importance of professionalization of adult education staff working with migrants, emphasizing competence-oriented training to improve stress resilience and work effectiveness. Additionally, the study underscores the necessity of fostering a better work-life balance and tailoring training programs to address gender-specific motivational factors and stress triggers, ultimately enhancing educators’ well-being and integration of work outcomes. These insights can inform targeted development and support measures for educators in this field.